2014
DOI: 10.1007/s13277-014-2433-8
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin pathway in bone cancers

Abstract: The Wnt signaling pathway regulates some of the crucial aspects of cellular processes. The beta-catenin dependent Wnt signaling (Wnt/β-catenin) pathway controls the expression of key developmental genes, and acts as an intracellular signal transducer. The association of Wnt/β-catenin pathway is often reported with different cancers. In this study, we have reviewed the association of Wnt/β-catenin pathway with bone cancers, focusing on carcinogenesis and therapeutic aspects. Wnt/β-catenin pathway is a highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 54 publications
1
49
0
Order By: Relevance
“…Previous studies have indicated that the Wnt signaling pathway serves an important role in cell proliferation, differentiation, survival and apoptosis, and is implicated in various tumor types (20,21). In the present study, it was observed that hsa-miR-185-5p was significantly dysregulated in chordoma tissues and had the potential to target the Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have indicated that the Wnt signaling pathway serves an important role in cell proliferation, differentiation, survival and apoptosis, and is implicated in various tumor types (20,21). In the present study, it was observed that hsa-miR-185-5p was significantly dysregulated in chordoma tissues and had the potential to target the Wnt signaling pathway.…”
Section: Discussionsupporting
confidence: 52%
“…About twenty years ago, causal mutations in the LRP5 gene were identified to be involved in two rare bone disorders, which were related to the Wnt/β-catenin pathway (54)(55)(56). A number of reports were exploded to highlight the role of the Wnt/β-catenin pathway in the regulation of bone homeostasis (57)(58)(59). Recently, the most highlighted members of the LDLR family involved in the maintenance of bone metabolism were LRP5, LRP6, LRP4, and Apoer2 (26,60).…”
Section: Discussionmentioning
confidence: 99%
“…TC-1 protein functions as a positive regulator of the Wnt/β-catenin signaling pathway that regulates cell migration, polarity, and fate determination during embryogenesis. Mutations or epigenetic inactivation of elements of this pathway can lead to birth defects or cancer [38]. TC-1 is thought to competitively block interactions between β-catenin and a repressor protein, leading to upregulation of β-catenin target genes [39].…”
Section: Discussionmentioning
confidence: 99%